Evaluation of the Effects of Preeclampsia and Gestational Diabetes Mellitus on Endothelial Function - Ömür ALBAYRAK; Mehmet Ata TOPÇUOĞLU (Bezmiâlem Science)
Objective: Gestational diabetes mellitus (GDM) and preeclampsia are the most common medical complications of pregnancy. Both GDM and preeclampsia are risk factors for cardiovascular diseases (CVD) and atherosclerosis. Flow-mediated dilatation (FMD) is a good ultrasonographic marker of early atherosclerotic changes used to measure endothelial function. In this study; we evaluated FMD, an indicator of endothelial function, and investigated whether there was an increased risk of CVD in patients with a history of preeclampsia or GDM. Methods: The study was carried out with 104 patients who gave birth in the Obstetrics and Gynecology Clinic of Bolu Abant İzzet Baysal University Training and Research Hospital between January 2016 and January 2017. Thirty four patients with a history of preeclampsia, 37 patients with a history of GDM, and 33 patients with uncomplicated deliveries were included in the study. All patients in the study had only one live birth and their age range was between 20 and 30 years. Demographic data, cardiovascular risk markers, obstetric data, laboratory tests and FMD change (%) measurements of all patients were compared. Mean and standard deviation values of the obtained data were calculated. Results: The mean FMD change (%) in the group of patients with a history of preeclampsia was 9.8±3.1. It was 10.32±2.50 in the group of patients with a history of GDM and it was 13.19±3.03 in the control group. A statistically significant difference was found between the control group and GDM and preeclampsia groups in terms of FMD change (%) (<0.001). There was a significant negative correlation between FMD change (%) and systolic blood pressure, diastolic blood pressure, the amount of proteinuria, and glucose, low-density lipoprotein and total cholesterol levels. Conclusion: The use of FMD change (%) measurement in patients with a history of GDM and preeclampsia can be used as a predictive marker for CVD, and early detection of risk can be time-consuming in terms of prevention. Demonstrating that GDM and preeclampsia cause increased cardiovascular risk in women’s lives will raise awareness of taking measures to reduce the risk in this group of patients.